Associations between different triglyceride glucose index-related obesity indices and sarcopenia: a cross-sectional study - Xiao, Wentao; Xu, Taichuan; Liao, Yitao; Xu, Yenan; Fan, Zhihong; Li, Chao; Zhang, Xian (Frontiers in Endocrinology, 2025)
BackgroundThe relationship of triglyceride glucose (TyG) index-related obesity indices with sarcopenia has not been studied in the U.S. population.MethodsThis cross-sectional survey utilizes data collected from the National Health and Nutrition Examination Survey spanning 2011 to 2018. The correlation between TyG-waist-to-height ratio (TyG-WHtR), TyG-weight-adjusted waist index (TyG-WWI), TyG-waist circumference (TyG-WC), TyG-body mass index (TyG-BMI), and sarcopenia was analyzed by weighted multivariate logistic regression using smoothed curves fitted to the observed nonlinear relationships and subgroup analysis were performed as well as an interaction test. Ultimately, the diagnostic validity of the four indices was evaluated in comparison with the TyG index for sarcopenia utilizing receiver operating characteristic (ROC) analysis.ResultsThis study included a total of 4804 participants, with 428 of those diagnosed with sarcopenia. The study illustrated that TyG-WHtR, TyG-WWI, TyG-BMI, and TyG-WC demonstrated a notable positive association with odds of sarcopenia prevalence [TyG-WHtR: OR (95% CI): 1.51(1.33, 1.72); TyG-WWI: OR (95% CI): 1.21 (1.18, 1.24); TyG-BMI: OR (95% CI): 1.15 (1.13, 1.18), TyG-WC: OR(95%CI):1.70(1.55, 1.87)]. Compared to the lowest quartile, the top quartile had a higher prevalence of sarcopenia, such as TyG-WWI (OR= 81.89, 95% CI: 38.49, 174.22). Subgroup analysis uncovered notable disparities in the relationship between four indices with sarcopenia., across gender and BMI≥30 strata. The association between the four distinct indices and sarcopenia is nonlinear. The ROC analysis demonstrated that four indices exhibited superior diagnostic efficacy to TyG. In addition, the diagnostic validity of TyG-WWI was optimal [TyG: AUC(95%CI):0.668(0.642,0.694); TyG-WHtR: AUC(95%CI):0.714(0.688,0.739); TyG-WC: AUC(95%CI):0.715(0.691,0.739); TyG-BMI: AUC(95%CI):0.737(0.714,0.761); TyG-WWI: AUC (95%CI):0.802(0.783,0.821)].ConclusionsTyG-WWI, TyG-WHtR, TyG-BMI, and TyG-WC are significantly positively linked to the prevalence of sarcopenia and outperform the TyG index in predicting this disorder. The TyG-related obesity indices, specifically the TyG-WWI index, have potential as reliable indicators for assessing and predicting sarcopenia.